ANALISIS TINDAK PIDANA PENCABULAN DI KABUPATEN ENREKANG (Studi KasusaPutusan 16Pid.Sus/2020/PN. Ekg): ANALYSIS OF THE CRIME OF LAW IN ENREKANG DISTRICT (Case Study Decision 16Pid.Sus/2020/PN. Ekg) - Tahir, Abd. Azis; Madiong, Baso; Shadiq, Amil (Faculty Of Law Bosowa University, 2021)
Thisastudy aims to identify the untraceable behaviors of sexually perverted criminals against children under the jurisdiction of law and law enforcement agencies in dealing with sexual abuse. The investigative method uses a criminological approach. That is, the investigation and discussion of the facts acquired according to the events that have occurred and on the basis of common legal standards andaexisting theories. This typeaof survey is descriptive and uses a dataasource that contains primaryaandasecondary data, namely primary, secondaryaand tertiary sources. Data interviews, interviews, survey methods, then the data is qualitatively analyzed. The results show that the uncertainty of the criminal act of sexual immorality between committing violence or threats of child violence, committing tricks, committing lies, or persuading children who have intercourse with him or other people and the factors causing the crime of sexual immorality include factors of violence, displacement, deliberately, deception. trickery, cajoling, copulation. Law enforcement efforts in overcoming these criminal acts are preemptive, preventive and repressive measures.